Education on Food Expiration Dates to Reduce Household Food Waste: Study in Urban Households - Prita Dhyani Swamilaksita; Reona Halimatusaa’dia; Anugrah Novianti; Kurnia Dwi Juliani; Elysia Rafa Azzahrah (PT.Mantaya Idea Batara, 2026)
Background: Food waste remains a significant challenge in Indonesia, particularly within urban areas. This study evaluated the impact of educational interventions regarding food expiration dates on mothers’ knowledge and food waste behavior in urban households in the Tanah Sareal District, Bogor City Methods: A quasi-experimental, one-group pre-test and post-test design was implemented with 55 housewives. The intervention used posters and balanced nutrition modules that emphasized food storage and expiration date labeling. Data were collected through a validated questionnaire and analyzed using descriptive statistics, paired t-tests, and chi-square tests. Result: Results indicated a significant increase in mothers’ knowledge, from 26.87 ± 3.91 before the intervention to 29.16 ± 1.31 after the intervention (p=0.0001). Food waste behavior also improved, as the average amount of food waste decreased from 73.44 ± 48.06 grams to 31.99 ± 27.30 grams (p=0.0001). Additionally, a significant association between knowledge and food waste behavior was observed following the intervention (p=0.022). Conclusion: These findings indicate that education about food expiration dates can enhance knowledge and reduce food-waste behavior among urban households. Community-based educational interventions employing simple visual media may offer an effective strategy for reducing food waste and promoting sustainable household food management.